1973
DOI: 10.1111/j.1365-2184.1973.tb01634.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Proliferation and Differentiation of Foetal Granulocyte‐macrophage Progenitor Cells in Haemopoietic Tissue*

Abstract: Analysis of in vitro colony formation in agar cultures of foetal haemopoietic tissues of eight mammalian species has shown that granulocyte‐macrophage progenitor cells are present in foetal liver, yolk sac, marrow and spleen in numbers approaching the incidence in adult marrow. Such characteristics as buoyant density, growth rate and differentiation served to distinguish foetal from adult colony forming cells (CFCs). Cell cycle analysis performed by exposing haemopoietic cells to high doses of tritiated thymid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The forms of myelopoiesis detected in this study correspond with those reported in the adult bone marrow and fetal rat liver (Ackerman, 1968;Bentfeld et al, 1977;Deimann and Fahimi, 1978). In addition, the predominance of monocytes over granulocytes in the fetal liver supports the hypothesis that the liver hemopoietic environment may be biased in favor of monocyte production at early gestational stages (Moore and Williams, 1973).…”
Section: Myelopoiesissupporting
confidence: 87%
“…The forms of myelopoiesis detected in this study correspond with those reported in the adult bone marrow and fetal rat liver (Ackerman, 1968;Bentfeld et al, 1977;Deimann and Fahimi, 1978). In addition, the predominance of monocytes over granulocytes in the fetal liver supports the hypothesis that the liver hemopoietic environment may be biased in favor of monocyte production at early gestational stages (Moore and Williams, 1973).…”
Section: Myelopoiesissupporting
confidence: 87%
“…The contribution of proliferating progenitors to (pre)osteoclast development during culture of 17-day-old bones is obviously a minor one. In this age group the number of bloodborne progenitors may be lowered owing to the declining number of circulating progenitor cells, as a result of the diminishing hemopoietic activity of the liver during the late embryonic and neonatal development (Moore and Williams, 1973;Burger et al, 1984). Furthermore, a limitation of the proliferation ability of the present immature osteoclast progenitors due to the advanced developmental stage of the 17-day-old bones may in part account for the small participation of these cells in osteoclast kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Hemopoietic colony-forming cells (CFC) are not homogeneous, but consist of subpopulations of progenitor cells at different stages of differentiation and maturation. Mouse bone marrow CFU-c which give rise to macrophage and neutrophil progeny are heterogeneous in their physical characteristics (24,25) and responsiveness to different molecular species of CSF (26). We now demonstrate that CFU-c populations committed to macrophage differentiation are differentially inhibited by prostaglandins of the E series.…”
Section: Discussionmentioning
confidence: 99%